Rileggendo i Minima moralia a cinquantun anni dalla scomparsa di Adorno. Nota pedagogica - Franco Cambi (Firenze University Press, 2020)
The Adornian theories are still a relevant theoretical and educational model, even fifty years after his death. The article develops exactly this aspect in many directions and it lingers on one of the masterpieces of the master of Frankfurt, Minima moralia, making use of hermeneutic critical thinking.